Impact of sanitary and phytosanitary measures on GCC meat imports - bahri, hichem (Journal of Excellence for Economics and Management Research, 2025)
This study aims to evaluate the impact of sanitary and phytosanitary (SPS) measures on meat trade, by applying it to the Gulf Cooperation Council (GCC) countries during the period 2003-2022, adopting the descriptive-analytical approach and using the gravity model of trade to answer the research question. The results of the current study show that SPS measures had a positive and statistically significant impact on meat imports, indicating that the health requirements of GCC countries are catalysts for exporting countries to increase their meat exports. Therefore, SPS measures have a positive impact on trade between countries if exporting countries can align their products with the health requirements of importing countries, which provides reassurance to consumers about the safety of products and increases their demand for them